Penggabungan Natural User Interface dengan Joypad pada Role Playing Video Game (RPG) - Sandhi Wistara; Wibisono Sukmo Wardhono; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Game with RPG as it's theme is placing player in world created with rule and story for player to experience. In this theme player given skill or magic based on rule in the world that created. The game with this kind of theme usually met in computer device. While consol device need adjustment to accommodate it's lack of input. To tacle this problem an outside input is needed to provide joypad lack of input. In this research Kinect is used that came with new X-box. This device use to capture human body joint to create data from it. From capture picture kinect turn it into bunch of data that can be manipulated and use. The type of data used in this research is head coordinate, left hand coordinate and right hand coordinate. Head coordinate is used to pin point user position. Right hand and Left hand is used to make input. The distance between both hand is used to decide whenever user making input or not. If by certain threshold the hand is far from each other kinect will wait till player making Lasso Form in one of the Hand. After Lasso is formed then it will became Function as Trigger. Trigger is used to decide the kind of input hand is making. From this research eight input is made with four on each hand.